EFFECT OF CORN DDGS ON EXTRUSION PROCESSING PARAMETERS AND PHYSICAL QUALITY OF EXTRUDED CATFISH FEED - Ilić, Petar (Journal on Processing and Energy in Agriculture, 2024)
Four iso-nitrogenous European catfish (Silurus glanis) diets (protein content approximately 400 g/kg) with the inclusion of 0, 100, 200 and 300 g/kg of corn DDGS were formulated and processed by twin-screw extruder. The aim was to assess the influence that DDGS has on extrusion processing and physical quality properties of sinking feed. All ingredients of the diets were finely ground at the hammer mill, mixed and steam conditioned to a temperature of 95 °C and moisture content of approximately 250 g/kg prior to the extrusion. The conditioned mixtures were processed by twin-screw extruder in order to produce sinking pellets. The DDGS inclusion in catfish diets decreased specific mechanical energy during extrusion, which significantly (p < 0.05) decreased radial expansion of the product when DDGS was included at levels of 200 and 300 g/kg. The inclusion of corn DDGS at levels of 100 and 200 g/kg resulted in pellets with significantly higher hardness and durability (p < 0.05) and without significant changes (p > 0.05) in water stability compared with the control feed. Corn DDGS proved not just as relatively cheap protein source in aquafeed but also as techno-functional ingredient that reduces the cost of feed production while giving extruded fish feed of increased ability to withstand mechanical stress during transport, storage and pneumatic feeding.